2002
DOI: 10.1289/ehp.02110119
|View full text |Cite
|
Sign up to set email alerts
|

Chronic arsenic poisoning from burning high-arsenic-containing coal in Guizhou, China.

Abstract: Arsenic is an environmental hazard and the reduction of drinking water arsenic levels is under consideration. People are exposed to arsenic not only through drinking water but also through arsenic-contaminated air and food. Here we report the health effects of arsenic exposure from burning high arsenic-containing coal in Guizhou, China. Coal in this region has undergone mineralization and thus produces high concentrations of arsenic. Coal is burned inside the home in open pits for daily cooking and crop drying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
83
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(87 citation statements)
references
References 15 publications
(21 reference statements)
3
83
0
1
Order By: Relevance
“…Although it was not possible to discriminate between As (K α ) and Pb (L α ) in this study, the existence of both elements, which has been identified as hazardous air pollutants, was already found in raw coal. Liu et al (2002) reported the health effects of arsenic exposure from burning coal which was burned inside the home in open pits for daily cooking and crop drying in China. Miller et al (1998) also detected Pb (12.8 ppm) in raw coal through the emissions testing in the pilot-scale combustor.…”
Section: Feed Coal Propertiesmentioning
confidence: 99%
“…Although it was not possible to discriminate between As (K α ) and Pb (L α ) in this study, the existence of both elements, which has been identified as hazardous air pollutants, was already found in raw coal. Liu et al (2002) reported the health effects of arsenic exposure from burning coal which was burned inside the home in open pits for daily cooking and crop drying in China. Miller et al (1998) also detected Pb (12.8 ppm) in raw coal through the emissions testing in the pilot-scale combustor.…”
Section: Feed Coal Propertiesmentioning
confidence: 99%
“…According to the IARC, skin shows the strongest association between chronic arsenic exposure and cancer (IARC, 2004), and dermal manifestations such as hyperpigmentation and hyperkeratosis are diagnostic of chronic arsenicosis. Arsenical hyperkeratosis appears predominantly on the palms of the hands and soles of the feet (Liu et al, 2002). Two-dimensional gel electrophoresis has been applied in arsenic-related proteomic studies (Yu et al, 1993), but this method has the disadvantages of low reproducibility, poor representation of low abundant proteins, inaccurate quantification, high labor and time requirements, and inability to analyze the membrane and hydrophobic proteins (Abdallah et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Oral exposure (in drinking water or food) or inhalation exposure (burning arsenic-containing coal) to inorganic arsenic impairs multi-organ (skin, liver, lung, kidney, and brain) function and eventually induces cancers in humans (Bates et al, 1992;Chen et al, 1988Chen et al, , 1992Chiou et al, 1995Chiou et al, , 2001IARC, 1987;Liu et al, 2002;NCR, 1999). In the inorganic arsenic compounds, arsenic exists either in trivalent (arsenite) or pentavalent form (arsenate), and inorganic pentavalent arsenic is the main form of contaminated drinking water in an endemic area of chronic arsenicism in China (Chiou et al, 2001;Pi et al, 2002).…”
Section: Introductionmentioning
confidence: 99%